Immunoreactive trypsinogen levels in newborn screened infants with an inconclusive diagnosis of cystic fibrosis - Chee Y. Ooi; Rosie Sutherland; Carlo Castellani; Katherine Keenan; Margaret Boland; Joe Reisman; Candice Bjornson; Mark A. Chilvers; Richard van Wylick; Steven Kent; April Price; Dimas Mateos-Corral; et al. (BMC, 2019)
Abstract Background Newborn screening (NBS) for cystic fibrosis (CF) not only identifies infants with a diagnosis of CF, but also those with an uncertain diagnosis of cystic fibrosis (CF), i.e. CF transmembrane conductance regulator (CFTR)-related metabolic syndrome (CRMS) or CF screen positive inconclusive diagnosis (CFSPID). These infants have an uncertain long-term outcome and it is currently unclear around time of diagnosis, which infants are at higher risk of later fulfilling a CF diagnosis. In this study, we hypothesised that immunoreactive trypsinogen (IRT) levels, used in NBS as a marker of pancreatic disease and function, may reflect the degree of CFTR dysfunction in each individual and therefore would help to identify those with CRMS/CSPID who are later at risk for meeting the criteria of CF. Methods In this longitudinal, prospective study, infants with CRMS/CFSPID and CF were recruited and followed in 9 CF clinics (Canada and Italy). We compared NBS IRT levels between CF and CRMS/CFSPID, and between children with CRMS/CFSPID→CF and CRMS/CFSPID→CRMS/CFSPID during the period of June 2007 to April 2016. Results Ninety eight CRMS/CFSPID and 120 CF subjects were enrolled. During the study period, 14 (14.3%) CRMS/CFSPID subjects fulfilled the diagnostic criteria for CF (CRMS/CFSPID→CF), while the diagnosis remained uncertain (CRMS/CFSPID→ CRMS/CFSPID) in 84 (85.7%) subjects. Significantly higher NBS IRT concentrations (ng/ml) were present in CF than CRMS/CFPSID (median (interquartile range): 143.8 (99.8-206.2) vs. 75.0 (61.0-105.9); P < 0.0001). Infants with CRMS/CFSPID→CF (n = 14) had significantly higher NBS IRT concentrations (ng/ml) than CRMS/CFSPID→ CRMS/CFSPID (n = 83) (median (interquartile range): 108.9 (72.3-126.8) vs. 73.7(60.0-96.0); P = 0.02). Conclusions Amongst infants who tested positive on NBS for CF, there is a gradation of elevated NBS IRT concentrations. Infants with CF have higher NBS IRT levels than CRMS/CFPSID, and higher NBS IRT concentrations were present in infants with CRMS/CFSPID→CF than CRMS/CFSPID→ CRMS/CFSPID. NBS IRT concentrations, in concert with other factors, may have the potential to predict the likelihood of CF amongst infants with CRMS/CFSPID.